Common bean through a participatory approach in Honduras. - Rosas, Juan Carlos (2003)
This work presents the results of the applicationof participatory methods for the genetic improvement ofbeans in two regions of Honduras. The methodology andresults obtained from the evaluation and selection activities,from early generation to advanced trials compare the linesselected by conventional and participatory methods, and thetrials to estimate the potential of adoption of promising lines,are shown and described. Evaluation and selection criteriaused by farmers to choose promising lines and varieties arementioned. The results are discussed, trying to explain themaccording to the basic plant breeding principles and practicesfor the improvement of cultivated plants. Finally, the benefitsof participatory plant breeding for farmers are identified,including those that are related to knowledge and skillacquisitions, and the increase on individual and collectivecapacity to take decisions; as well as the advantages forbreeding programs under these participatory approaches.